A Singular Disclosure Requirement Is Necessary For Patent Law - Falati, Shahrokh (Science and Technology Law Review, 2023)
The Court of Appeals for the Federal Circuit’s recent jurisprudence on 35 U.S.C. § 112 has selectively and severely curtailed innovation in the fields of pharmaceuticals and biotechnology. Specifically, the Federal Circuit’s shifting position on 35 U.S.C. § 112 and their evolving jurisprudence to combine expanding the application and scope of the written description requirement with a separate, heightened standard for enabling claims directed to innovation in a genus of therapeutic antibodies, or a genus of compounds having functional limitations, has caused havoc in the biopharmaceutical industry. Federal Circuit jurisprudence on how to interpret the disclosure requirements of the 35 U.S.C. § 112 contravenes the statute and Supreme Court precedent by mandating two separate disclosure requirements in place of one, namely that patent applications not only “enable” but also separately “describe” inventions. This recently developed and reactively evolving judge made approach raises the bar exceedingly high for obtaining any meaningful patent protection for new biomedical discoveries, goes against many decades of patent practice, and is proving to be a powerful impediment to the investment necessary for developing new and lifesaving medicines. This article examines patent law’s current disclosure requirements to highlight a failing judicial trajectory and proposes a return to a single 35 U.S.C. § 112(a) standard. By doing so, the great shock that has singled out and disrupted the biopharmaceutical industry will be removed and the law can once again encourage, in a technology-neutral manner, the private sector to innovate in all fields of endeavor, including encouraging the biopharmaceutical industry to develop new lifesaving medicines and treatments.